2006
DOI: 10.1007/s11199-006-8870-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Stereotypes About Gay Men

Abstract: Three studies were conducted to examine the mental health stereotypes about gay men among college student and therapist trainee samples. Results from Study 1 indicated that (a) college students and therapist trainees endorsed a stereotype of the mental health of gay men that was similar in terms of its content and strength, and (b) the stereotype was consistent with five DSM-IV-TR disorder categories: mood, anxiety, sexual and gender identity, eating, and personality disorders. In Study 2 and 3 we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
2
29
1
2
Order By: Relevance
“…This might include discussing the stereotypes that gay men and lesbians are more likely to be addicts, to be depressed, and/or to have body image issues than their heterosexual counterparts. Boysen, Vogel, Madon, and Wester (2006) suggested that such mental health stereotypes influence the quality of psychotherapy provided to queer people. Counselor educators are encouraged to infuse in-class activities that help students to analyze these stereotypes along with the connections that exist between them and the general oppression of queer people in society.…”
Section: Heterosexism: Strategies For Counselor Training and Educationmentioning
confidence: 99%
“…This might include discussing the stereotypes that gay men and lesbians are more likely to be addicts, to be depressed, and/or to have body image issues than their heterosexual counterparts. Boysen, Vogel, Madon, and Wester (2006) suggested that such mental health stereotypes influence the quality of psychotherapy provided to queer people. Counselor educators are encouraged to infuse in-class activities that help students to analyze these stereotypes along with the connections that exist between them and the general oppression of queer people in society.…”
Section: Heterosexism: Strategies For Counselor Training and Educationmentioning
confidence: 99%
“…As the co-participants in this study revealed, experiencing a same-sex attraction is, in and of itself, extremely stress-provoking. Boysen, Vogel, Madon, and Wester (2006) examined the mental health stereotypes regarding gay men held by college students and therapists. Their study found that "gay men seek out counselling disproportionately more than their straight counterparts, and more largescale, representative, epidemiological studies have shown that gay men tend to suffer more frequently than straight men from certain mental health symptoms" (p. 70), including mood disorders, anxiety disorders, sexual and gender identity problems, and eating and personality disorders.…”
Section: Masculinitymentioning
confidence: 99%
“…Such a stereotype may reflect the historical period in which homosexuality was a diagnosable mental illness. Indeed, a recent study by Boysen et al (2006) found a specific mental health stereotype about gay men. The researchers presented college students and counselor trainees with a list of symptoms of mental illness and had them rate how characteristic the symptoms were of gay men.…”
Section: The Current Researchmentioning
confidence: 99%
“…Furthermore, individuals can possess stereotypes about their own social groups that affect beliefs and behaviors (Burkley & Blanton, 2009). Gay men are a social group that is the target of many stereotypes (Clausell & Fiske, 2005), and research indicates that one set of beliefs about gay men surrounds their mental health (Boysen, Vogel, Madon, & Wester, 2006). However, previous research does not indicate whether gay men hold a stereotype about their own mental health, the content of such a stereotype, or how it compares to mental health stereotypes about other groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation